2019
DOI: 10.3389/fnhum.2019.00331
|View full text |Cite
|
Sign up to set email alerts
|

Signal Processing in fNIRS: A Case for the Removal of Systemic Activity for Single Trial Data

Abstract: Researchers using functional near infrared spectroscopy (fNIRS) are increasingly aware of the problem that conventional filtering methods do not eliminate systemic noise at frequencies overlapping with the task frequency. This is a problem when signals are averaged for analysis, even more so when single trial data are used as in online neurofeedback or BCI applications where insufficiently preprocessed data means feeding back noise instead of brain activity or when looking for brain-behavior relationships on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…On the other hand, (Kirilina et al, 2012) reported HbR to be less sensitive to artifacts. However, a recent study (Klein and Kranczioch, 2019) demonstrated that HbR is also affected by a global signal component. The contrast-to-noise ratio seems to be comparable for HbO and HbR across different tasks (Cui et al, 2011), but according to Naseer and Hong (2015) HbO signals were more discriminative for BCI applications than those of HbR signals.…”
Section: Online Feature -Chromophores Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, (Kirilina et al, 2012) reported HbR to be less sensitive to artifacts. However, a recent study (Klein and Kranczioch, 2019) demonstrated that HbR is also affected by a global signal component. The contrast-to-noise ratio seems to be comparable for HbO and HbR across different tasks (Cui et al, 2011), but according to Naseer and Hong (2015) HbO signals were more discriminative for BCI applications than those of HbR signals.…”
Section: Online Feature -Chromophores Usedmentioning
confidence: 99%
“…Short-distance channels in combination with GLM seem to be the most efficient tool to correct for extracerebral physiological signal components (Brigadoi and Cooper, 2015;Tachtsidis and Scholkmann, 2016;von Lühmann et al, 2020). As already stated, only Fujimoto et al (2017) used this technique, which may be because most of the fNIRS systems are not equipped with the appropriate hardware (Klein and Kranczioch, 2019). If this is the case, a potential alternative is the global component removal approach as introduced by Zhang et.…”
Section: Online Preprocessing and Artifact Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-distance channels in combination with GLM seem to be the most efficient tool to correct for extracerebral physiological signal components (Brigadoi and Cooper, 2015 ; Tachtsidis and Scholkmann, 2016 ; von Lühmann et al, 2020 ). As already stated, only Fujimoto et al ( 2017 ) used this technique, which may be because most of the fNIRS systems are not equipped with the appropriate hardware (Klein and Kranczioch, 2019 ). If this is the case, a potential alternative is the global component removal approach as introduced by Zhang et al ( 2016 ).…”
Section: Online Signal-processing Methods and Hardwarementioning
confidence: 99%
“…An alternative method would be to employ short-distance channels (<1 cm), which were not available in the commercial optode holder cap used, to remove by regression hemodynamic fluctuations that co-occur in the cortex as well as superficial scalp layers (Gagnon et al, 2012;Tachtsidis and Scholkmann, 2016). Although we used bandpass filters and PCA to remove physiological inferences and global hemodynamic fluctuations, there exists several other different computational methods including (i) independent component analysis, (ii) singular value decomposition (SVD) and Gaussian kernel smoothing, (iii) statistical correction methods, (iv) wavelet-based methods, or (v) a combination of these methods can be used for removal (Huppert et al, 2009;Jang et al, 2009;Tachtsidis and Scholkmann, 2016;Cao et al, 2018b;Duan et al, 2018;Klein and Kranczioch, 2019). Thus, a quantitative comparison using different global component removal methods is warranted in future studies.…”
Section: Limitationsmentioning
confidence: 99%